METODE SELF HYPNOSIS UNTUK MENGATASI STRES MAHASISWA AKHIR JURUSAN BIMBINGAN DAN PENYULUHAN ISLAM PADA FAKULTAS DAKWAH DAN KOMUNIKASI UIN ALAUDDIN MAKASSAR - N, Khaeriyah; Alang, HM Sattu; Wulur, Maesil B (AL-IRSYAD AL-NAFS: JURNAL BIMBINGAN DAN PENYULUHAN ISLAM, 2021)
The study discusses the Self Hypnosis Method in dealing with the stress of final students majoring in Islamic guidance and counseling at the da'wah and communication faculty with subproblems, namely; (1) what causes final student stress, (2) how is the method of self-hypnosis in dealing with final student stress. (3) how are the obstacles in doing self-hypnosis and the solutions. The results of this study indicate that the causes of stress for final students at the da'wah and communication faculty are time pressure, difficulty finding supervisors, difficulty in finding references, and fear of work. The method of self-hypnosis in dealing with stress in students, namely relaxation, self-programming, and termination is done before going to bed and before leaving for campus.